WNT7A (rs104893832) polymorphism increases the risk of recurrent spontaneous abortion in Iranian women - Mazdapour, Manouchehr; Ashkezari, Mahmood Dehghani; Seifati, Seyed Morteza (Faculty of Medicine, Trisakti University, 2018)
BACKGROUNDRecurrent spontaneous abortion is defined as the occurrence of three or more clinical miscarriages in one woman. Several factors, including genetics and environmental factors, are involved in this kind of infertility, in which WNT7A (rs104893832) polymorphism plays a major role. The aim of the present study was to determine the association between a common polymorphism of WNT7A (rs104893832) with recurrent spontaneous abortion in females. METHODSIn the present case-control study, the WNT7A (rs104893832) polymorphism was investigated in 70 women with recurrent spontaneous abortion as cases and 100 women with at least one child and no history of infertility or abortion as controls. Polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP) was used to investigate the WNT7A (rs104893832) polymorphism in both case and control groups. The data were subsequently analyzed using the chi-square and logistic regression tests by SPSS software (version 18.0). RESULTSA significant association was found between the WNT7A (rs104893832) polymorphism and recurrent spontaneous abortion (OR=25.00, 95% CI=5.52-157.09; p<0.0001). Our finding showed that G allele frequency in women with recurrent spontaneous abortion was significantly different compared to the control group. (OR=6.42, 95% CI=2.82-15.16; p<0.0001).Therefore, genetic variation in WNT7A (rs104893832) polymorphism may play a role in recurrent spontaneous abortion. ConclusionThis study revealed that WNT7A (rs104893832) polymorphism increased the risk of recurrent spontaneous abortion. Knowledge of these mutations and polymorphisms can provide an insight into the prognosis for individual patients. Therefore, further studies are necessary to establish the association of WNT7A (rs104893832) polymorphism with recurrent spontaneous abortion in a larger population.